An Evaluation of Factors for Retaining Female Students in Construction Management Programs. Issue 1 (2nd January 2016) - Bigelow, Ben F.; Bilbo, David; Ritter, Lisa; Mathew, Minna; Elliott, Jonathan W.
ABSTRACT: The under-representation of women in construction necessitates academia's understanding of what influences a female's decision to remain in a construction management (CM) program. Many factors that retain women in CM programs have been identified. Understanding which of these factors are most influential is an important step towards increasing the number of women in CM. This study used a quantitative approach to explore the factors that have been previously identified to retain female students in CM programs; however, qualitative methods were also used to identify additional retention factors. The research was completed through a self-administered, researcher-designed survey of female CM students at five major universities. The results provide a prioritized ranking of the factors identified to retain female students. They indicated that the most positively influential factors for females to remain in a CM undergraduate degree program are: the community of students, lab classes, internships, innovation in the classroom, and student organizations. Job/Career opportunities also emerged as a positively influential factor for retention of female students that was previously not identified in the literature.